1905 N. Y. Laws 129-30, ch. 92, § 2 - (:unkn) unknown (General Publisher, 1905)
Prohibited anyone over the age of sixteen to carry or carry concealed any pistol, revolver, or other firearm without a licensed issued by a police magistrate. Also prohibited the use against another, carry, or possession of slung-shot, billy, sandclub, metal knuckles, dagger, or dangerous knife is guilty of a felony.
--
Keywords: CARRY - CONCEALED